(untitled) (Journal of Global Humanities and Social Sciences, 2023)
Brand image marketing is closely related to brand awareness and brand loyalty. Brand image marketing improves brand awareness and recognition through a variety of means and activities, thus enhancing consumers’ loyalty and willingness to purchase brands. Enterprises need to adopt corresponding brand image marketing strategies and tools according to market demand and their situation to enhance the brand image and competitiveness comprehensively. This paper first introduces the definition and objectives of brand image marketing and then focuses on the influence of brand awareness and loyalty on brand image marketing and the key factors affecting brand awareness and loyalty. Then, this paper illustrates how to achieve the goal of brand image marketing from the aspects of unified management of brand image, multi-channel marketing, and personalized marketing, and illustrates cases, which can provide reference and inspiration for enterprises to implement brand image marketing, and also provide new ideas and directions for the development of the industry.